(untitled) (Fiep Bulletin - online, 2014)
The health professionals face, in its environment of work, with situations that can take them it the diverse occupational risks, as well as industrial accidents. Nursing sector is the champion of accidents in the service of Brazilian health; being thus, the present study it has for objective to analyze Norma Regulamentadora 32 in the vision of the health worker. For its development, it was opted to the bibliographical research. In constant exposition to the most varied risks and situations the Brazilian service of health gained an ally, Norma Regulamentadora 32 is necessary to understand despite the subjects related to the health of the nursing worker cannot be analyzed separately, must be associates to the biological question, to the conditions of life in the work, as well as the determinative factors for risks of accidents and occupational illnesses. During the academic experience it was observed that one of the factors that contribute for the occurrence of accidents in the work it is the unfamiliarity of the risk agents whom they are gifts in day-by-day of the health professional. In this context, it is observed that for the prevention of accidents the knowledge is very important, the information concerning what it can happen after one cut, a bite, a contamination for some type of fluid of the patient, for example. It is extremely important that all the health professionals are informed on the related legislation, as well as demand adequate conditions of work mainly, exerting its paper while professional and citizens, who fulfill with its duties and demand its rights, of that to work with security